Tourism Development Strategy to Increase Local Original Income (PAD) in Bulukumba Regency - Nurmi Nurmi; Basri Bado; Citra Ayni Kamaruddin; Sri Astuty; Muhammad Imam Maruf (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the tourism development strategy to increase Local Original Revenue (PAD) in Bulukumba Regency, South Sulawesi. Despite having significant tourism potential, such as Bira Beach and the Pinisi shipbuilding tradition, the contribution of the tourism sector to PAD remains fluctuating and has not been fully optimized. Therefore, this study aims to formulate an effective and targeted tourism development strategy. The research employs a quantitative descriptive approach using observation, Likert-scale questionnaires, and documentation, with data analyzed through SWOT analysis, IFAS-EFAS matrices, and the Grand Strategy Matrix. The findings indicate that the tourism sector has strong internal strengths (5,09) and significant external opportunities (4,99), exceeding its weaknesses (4,56) and threats (3,95), placing it in Quadrant I (aggressive strategy). The results suggest that the most appropriate strategy is the SO (Strengths-Opportunities) strategy, which focuses on optimizing tourism potential, enhancing digital promotion, strengthening cultural-based tourism, and expanding investment in infrastructure. The study concludes that implementing an aggressive and integrated strategy can improve the tourism sector’s contribution to PAD and support regional economic development. These findings highlight the importance of aligning tourism potential with strategic planning to achieve sustainable fiscal growth.